Das Teologias da Prosperidade, do Neocalvinismo e da Transformação Social: um estudo histórico comparativo das igrejas Verbo da Vida e Cidade Viva - Ribeiro, Saulo Duarte Lima (2021)
This doctoral research aims to analyze two evangelical groups based on their main doctrines and their social performance, investigating the influence of these doctrines on the praxis of both, as well as the possible expected counterparts of the target audience of the actions. Considering that they are two distinct Protestant currents with particular specificities in the construction and doctrinal confession, but which mainly have the Bible as a sacred book and the main rule of faith, we chose to bring as a methodological theoretical support the bases of the social theology of the Christian church from the writings Old Testament biblical texts, passing through the teachings of Christ and the apostles on the subject, some Catholic encyclicals, the debates on Liberation Theology and Integral Mission Theology, materials by neo-Pentecostal leaders, to the writings of Protestant Abraham Kuyper and other formators of the movement called Neo-Calvinist, all focused on the social performance of the church, in order to reflect on what would come to be researched directly with volunteers and pastors from the two Protestant institutions. The two institutions have in their preached and followed theologies the construction of a cosmovision that does not end with public worship and rites proper to the structures of the temples, but enters into family, professional and social relationships in general, inferring and interfering with the whole, this includes social action with vulnerable publics. The work ends with the survey carried out with volunteers and pastors, in which we seek to answer which concepts differentiate them in their actions aimed at social transformation and what counterparts they expect from their target audience.